MATHEMATICS CONCEPT IN ELEMENTARY SCHOOL: A BIBLIOMETRIC ANALYSIS - Ork Sreylak; Falenthino Sampouw; Totok Victor Didik Saputro; Winda Lidia Lumbantobing (Journal of Educational Learning and Innovation (ELIa), 2022)
The purpose of this study was to describe the trend and development of research about the mathematics concept in elementary schools in Indonesia. This study was a literature review research using bibliometric analysis. The exploration process of the articles’ published results was taken through an open-access website such as google scholar database for the last ten years. The exploration of articles published results used Harzing’s Publish or Perish software with the keywords “Konsep Dasar Matematika Sekolah Dasar” and “Mathematics Concept in Elementary School”. The results of the exploration process were analyzed by using VOSviewer software for visualization and relationship for all of the research results. This study’s results showed there were 1185 articles had been published based on articles exploration criteria. After reducing the data, there were 37 articles with the relevant criteria. The bibliometric analysis results of the relevant articles were the understanding of student mathematics concepts in elementary school, the pre-service students and teacher knowledge about the mathematics concept in elementary school, and the solution for improving students’ understanding of mathematics concepts in elementary school